2019
DOI: 10.3390/d11080128
|View full text |Cite
|
Sign up to set email alerts
|

Parageobacillus thermantarcticus, an Antarctic Cell Factory: From Crop Residue Valorization by Green Chemistry to Astrobiology Studies

Abstract: Knowledge of Antarctic habitat biodiversity, both marine and terrestrial, has increased considerably in recent years, causing considerable development in the studies of life science related to Antarctica. In the Austral summer 1986–1987, a new thermophilic bacterium, Parageobacillus thermantarcticus strain M1 was isolated from geothermal soil of the crater of Mount Melbourne (74°22′ S, 164°40′ E) during the Italian Antarctic Expedition. In addition to the biotechnological potential due to the production of exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 113 publications
(150 reference statements)
0
14
0
Order By: Relevance
“…In our study, a cellulase producing thermophilic bacterium, Parageobacillus thermoglucosidasius NBCB1 was isolated from a thermophilic bacterial consortium bred from vermicompost using RS as substrate. P.thermoglucosidasius has earlier been isolated from soil [32], marine environment [33], compost [34], wood wastes [35] and hot springs [36]. However, there are limited reports on the production of enzymes by the organism.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a cellulase producing thermophilic bacterium, Parageobacillus thermoglucosidasius NBCB1 was isolated from a thermophilic bacterial consortium bred from vermicompost using RS as substrate. P.thermoglucosidasius has earlier been isolated from soil [32], marine environment [33], compost [34], wood wastes [35] and hot springs [36]. However, there are limited reports on the production of enzymes by the organism.…”
Section: Discussionmentioning
confidence: 99%
“…In events of oil slick, EPS acts as an emulsifier binding oil droplets (hydrocarbon) with other organic matter forming marine oil snow. (Carrión et al, 2015;Caruso et al, 2018aCaruso et al, , 2018bCaruso et al, , 2019Corsaro et al, 2004;Daglio et al, 2018;Finore et al, 2019;Manca et al, 1996; J o u r n a l P r e -p r o o f…”
Section: Perspectives and Future Prospectsmentioning
confidence: 99%
“…The taxonomical assignment of strain M1 underwent several changes over the years. Originally, at the time of the first taxonomic description, Nicolaus et al (1996) indicated it by the name of Bacillus thermoantarcticus , which was subsequently corrected to “ thermantarcticus ” in the Validation List N. 84 published in IJSEM ( Finore et al, 2019 ). Based on the 16S rRNA gene sequence analysis, strain M1 was placed as a peripheral member of the thermophilic Bacillus rRNA group 5.…”
Section: Introductionmentioning
confidence: 99%